PENGARUH SUHU DAN WAKTU EKSTRAKSI TERHADAP KARAKTERISTIK PEWARNA ALAMI BUAH PANDAN (Pandanus tectorius) - Arik Cahayanti, Ida Ayu Putu; Wartini, Ni Made; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 2 (2016): Juni)
The aims of this study were to determine the effect of temperature and extraction time on the natural colorant characteristics of pandanus fruit and to obtain the right temperature and extraction time to produce with the best characteristics natural colorant of pandanus fruit.This study used a factorial randomized block design. The first factor was the temperature which consists of four levels: 45 o C, 60 o C, 75 o C and 90 o C. The second factor was the extraction time which consists of three levels: 120, 240 and 360 minutes. The results showed that the temperature affect the yield, total carotenoid and color strength. The temperature and extraction time affect the color strength. The interaction of temperature and extraction time have no effects on the extraction yield, total carotenoid, the level of brightness (L*), the level of redness (a*), the level of yellowness (b*). Based on effectivity index analysis the product had the interaction of temperature of 45 o C and extraction time of 360 minutes produce the best of natural colorant extract of pandanus fruit with the following characteristics: 3,05% of yields, 0,45% of total carotenoid contents, 4,83 of the brightness level (L*), -2,45 of the redness level (a*), 34,96 of the yellowness level (b*), and 10,3 of the color strength (powerful). Keywords: extraction temperature, extraction time, natural colorant, pandanus fruit
Keywords: 95,